Evaluación del piloto de inyección de agua implementado en un campo de crudo pesado de la cuenca de los Llanos Orientales para el diseño de estrategias de optimización del proceso (2019)
Oil recovery by injecting fluids into the reservoir has been one of the recovery methods with the greatest impact on increasing oil production worldwide. According to the operational requirements and conditions under which a deposit is found, water or gas injection operations are carried out. The first, whether externally or internally, has the purpose of recovering the remaining oil by generating a physical sweep of the porous medium, displacing the oil to the producing wells associated with the injector well. Despite this, to apply this recovery technology is necessary to consider a series of parameters that support its development in the field. Projects like this aim to evaluate the different parameters involved in the development of the waterflooding pilot carried out in a heavy oil field located in the Llanos Orientales Basin, for the design of process optimization strategies, prior to the phase of expansion of this technology.